Air Quality Assessment of Faisalabad and Gujranwala Cities of Pakistan: Application of Pollution Indices - Faiz, Y.; Waheed, S.; Siddique, N. (The Nucleus, 2015)
Urban air quality of industrial cities of Pakistan, namely Gujranwala and Faisalabad was assessed in terms of pollution level indicators such as pollution load index (PLI), geoaccumulation index (Igeo), pollution index (PI) and integrated pollution index (IPI). It was found that both cities have elevated metal concentrations indicating heavy to extreme contamination for most of the sites. Local anthropogenic activities and elevated geo-accumulation indices for different suite of elements were used to indicate possible pollutant sources in these two industrial cities to be traffic derived emissions, suspended soil, road dust, construction materials, fossil fuel and industrial emissions, tanneries, chrome plating units and metal smelters. Comparison of the pollution indices shows that Ba, Br, Ca, Cd, Na, Pb, Sb and Zn have mean PLI, Igeo, PI and IPI for both cities which are in the highly polluted category. Cu, La, Sc, V and Zr have pollution indices corresponding to high or extreme levels in Faisalabad only while Cr and Ti are highly polluting only in Gujranwala. In Faisalabad and Gujranwala it was found that 91.43 % and 85.29 % respectively of the PI data occurs in high level of pollution implying that to some extent Faisalabad is more polluted as compared to Gujranwala.